Co-designing inflammatory bowel disease (Ibd) services in Scotland: findings from a nationwide survey. Issue 1 (December 2016) - Schoultz, Mariyana; Macaden, Leah; Watson, Angus
Abstract Background The Scottish Government's ambition is to ensure that health services are co-designed with the communities they serve. Crohn's and Colitis UK and the Scottish Government acknowledged the need to review and update the current IBD care model. An online survey was conducted asking IBD patients about their experiences of the NHS care they receive. This survey was the first step of co-designing and developing a national strategy for IBD service improvement in Scotland. Aim: To explore IBD patients' experiences of current services and make recommendations for future service development. Methods This study was part of a wider cross-sectional on-line survey. Participants were patients with IBD across Scotland. 777 people with IBD took part in the survey. Thematic analysis of all data was conducted independently by two researchers. Results Three key themes emerged: Quality of life: Participants highlighted the impact the disease has on quality of life and the desperate need for IBD services to address this more holistically. IBD clinicians and access: Participants recognised the need for more IBD nurses and gastroenterologists along with better access to them. Those with a named IBD nurse reported to be more satisfied with their care. An explicit IBD care pathway: Patients with IBD identified the need of making the IBD care pathway more explicit to service users. Conclusions Participants expressed the need for a more holistic approach to their IBD care. This includes integrating psychological, counselling and dietetic services into IBD care with better access to IBD clinicians and a more explicit IBD care pathway.